The Thought of Politics - Resta, Eligio (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
The relationships between politics and technology are today very complex. According to E. Bloch we can speak about a “discontinuos continuity”. Technology was able to change sense, perceptions and attitudes of political action only where political systems are reduced to searching consensus by governments (may be the post-politics). In the contemporary systems political action is stressed to make relevants political items, indipendently from the real consistency of deliberation (the lack of democracy). In such a way technology becomes the “essence” of politics. But the public sphere is not only linked with simple relevance of themes. So we need to turn to a deeper, classic, political thought. Keywords: Politics, Technology, Relevance of Themes, Public Sphere.